Damage Evolution Due to Extremely Low-Cycle Fatigue for Inconel 718 Alloy - Mohammed Algarni; Yuanli Bai; Mohammed Zwawi; Sami Ghazali (Metals, 2019)
This paper evaluates the damage evolution process under extremely low-cycle fatigue (ELCF). The study explores the damage behavior under different stress states. The influence of the multiaxial state of stress on the metal’s life is determined. Two different stress states were examined: (a) axisymmetric and (b) plane-strain. The study is based on the modified Mohr−Coulomb (MMC) ductile fracture criterion that was extended to cover the ELCF regime in a previous research study. Four distinctive geometries are designed to study the effect of different stress states on ELCF life and damage evolution. The damage model is calibrated for life prediction to agree with the ELCF experimental results. The investigation of the damage evolution behavior is dependent on equivalent plastic strain, stress triaxiality, Lode angle, and cyclic loading effect. The damage evolution is extracted from Abaqus finite element simulations and plotted versus the equivalent plastic strain. The damage accumulation shows nonlinear evolution behavior under cyclic loading conditions. SEM images were taken to further study the microscopic failure mechanisms of ELCF.